2023
DOI: 10.4103/bc.bc_37_23
|View full text |Cite
|
Sign up to set email alerts
|

No-reflow phenomenon following stroke recanalization therapy: Clinical assessment advances: A narrative review

Yuan Kan,
Sijie Li,
Bowei Zhang
et al.

Abstract: The no-reflow phenomenon (NRP) after successful vascular recanalization in acute ischemic stroke (AIS) has become a major cause of poor clinical prognosis and ineffective recanalization. However, there is currently no clear definition or unified clinical assessment method for the NRP. Therefore, it is urgent to clarify the clinical evaluation criteria for the NRP and develop new no-reflow evaluation techniques so that remedial treatment can be applied to AIS patients suffering from the NRP. In this brief revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…A significant difference was observed in the median 24-hour NIHSS scores among the 4 groups (P=0.008). In pairwise comparisons, significant differences were observed in the median 24-hour NIHSS scores in comparison to both the NBO-4h (6 [IQR, [4][5][6][7][8][9][10][11][12]) and the NBO-6h (7 [IQR, [5][6][7][8][9][10][11][12]) groups with the control group (11 [IQR, [3][4][5][6][7][8][9][10][11][12][13]; P=0.007 and P=0.010, respectively) and the NBO-2h groups (10 [IQR, 7-14]; P=0.02 and P=0.029, respectively). However, no significant differences were observed between the NBO-2h group and the control group or between the NBO-4h group and the NBO-6h group (Table 3; see pairwise comparisons in Table S1).…”
Section: Secondary Efficacy Outcomesmentioning
confidence: 98%
See 3 more Smart Citations
“…A significant difference was observed in the median 24-hour NIHSS scores among the 4 groups (P=0.008). In pairwise comparisons, significant differences were observed in the median 24-hour NIHSS scores in comparison to both the NBO-4h (6 [IQR, [4][5][6][7][8][9][10][11][12]) and the NBO-6h (7 [IQR, [5][6][7][8][9][10][11][12]) groups with the control group (11 [IQR, [3][4][5][6][7][8][9][10][11][12][13]; P=0.007 and P=0.010, respectively) and the NBO-2h groups (10 [IQR, 7-14]; P=0.02 and P=0.029, respectively). However, no significant differences were observed between the NBO-2h group and the control group or between the NBO-4h group and the NBO-6h group (Table 3; see pairwise comparisons in Table S1).…”
Section: Secondary Efficacy Outcomesmentioning
confidence: 98%
“…Significant differences in the 7-day NIHSS scores were observed among the 4 groups (P=0.04; Table 3). Pairwise comparisons revealed that the NBO-4h (5 [IQR, [2][3][4][5][6][7][8][9][10][11][12]) and NBO-6h (6 [IQR, 4-10]) groups had significant differences compared with the control group (9 [IQR, [7][8][9][10][11][12]; P=0.018 and P=0.027, respectively). However, there were no significant differences between the NBO-2h group and the control group (P>0.05) or between the NBO-4h group and the NBO-6h group (P>0.05); see pairwise comparisons in Table S1.…”
Section: Secondary Efficacy Outcomesmentioning
confidence: 99%
See 2 more Smart Citations